PROXIMATE ANALYSIS OF ROOT, STEM AND LEAVES OF MILLETIA AURICULATA - RAJESH P. GANORKAR; D. V. DEOGHARE; K.A.SHINGARWADE; Y. S. KHOLE (International Journal of Pharma and Bio Sciences, 2016)
This work was carried out to investigate the proximate analysis such as Moisture, ash content and cold water, hot water, 1% NaOH and HCl solubility of root, stem and leaves samples of Milletia Auriculata. This study showed that the studied root, stem and leaves of plant contained a low moisture content. These results directly hamper the drug effect, drug activities and also the side effects of drug. In rural areas where access to modern health facilities is limited by the level of development, plants/herbs remain the main stay of the health care system.